Avian infectious bronchitis and its management in Nepal: a review - Rana, Chandrakala; Bhattarai, Birat; Rana Magar, Khil Bahadur; Panth, Yuvraj (Journal of Agriculture and Natural Resources, 2021)
Avian infectious bronchitis (IB) is a highly contagious disease of poultry with high economic importance. Caused by avian infectious bronchitis virus (IBV), it is transmitted by direct and indirect contact through aerosol or fecal means. Although IB is considered as respiratory disease, various strains of IBV affect the renal as well as the reproductive system. The economic importance of disease is due to lower egg production, poor hatchability of eggs, and decreased quality of the egg, weight loss, growth retardation, and high condemnation rates in meat-type birds. Although the prevalence of IB is lower in Nepal (>1%), it is ranked second as a disease which claims most livestock unit in the world. There is no specific treatment for IB but live and inactivated vaccines are available for the prevention and control of the virus. The lack of research in the infectious bronchitis virus can cause production losses in poultry sector due to the evolution of resistant virus strain in our country. This review discusses the aspects of avian infectious bronchitis prevalence in Nepal.